2011
DOI: 10.1016/j.radonc.2011.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia imaging with [F-18] FMISO-PET in head and neck cancer: Potential for guiding intensity modulated radiation therapy in overcoming hypoxia-induced treatment resistance

Abstract: Background and Purpose Positron emission tomography (PET) imaging with [F-18] fluoromisonidazole (FMISO) has been validated as a hypoxic tracer [1, 2]. Head and neck cancer exhibits hypoxia, inducing aggressive biologic traits that impart resistance to treatment. Delivery of modestly higher radiation doses to tumors with stable areas of chronic hypoxia can improve tumor control [3]. Advanced radiation treatment planning (RTP) and delivery techniques such as Intensity Modulated Radiation Therapy (IMRT) can deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 44 publications
0
104
0
2
Order By: Relevance
“…Dose escalation for a hypoxic tumor is an important consideration for improving the effect of radiotherapy (23)(24)(25). The definition of hypoxic volume is essential for choosing the target for dose escalation.…”
Section: Discussionmentioning
confidence: 99%
“…Dose escalation for a hypoxic tumor is an important consideration for improving the effect of radiotherapy (23)(24)(25). The definition of hypoxic volume is essential for choosing the target for dose escalation.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic regions delineated by 18 F-FMISO-PET received a 20% dose escalation (84 Gy), while nontarget tissue doses were maintained below normal tissue tolerances, making this a feasible strategy for IMRT therapy planning. In a separate study in 10 H&NC patients, IMRT planning and dose escalations using 18 F-FMISO PET imaging data was shown to increase tumor control probability by an average of 17% as a result of the modeled dose increases (119). Dose painting by numbers (DPBN), which escalates radiation doses based on the intensity of the 18 F-FMISO PET imaging data, enabled additional precision in therapy planning over uniform dose estimates (uniDE) derived from 18 F-FDG (265,266).…”
Section: A Use Of Hypoxia Information In Radiation Therapy Planningmentioning
confidence: 94%
“…Hypoxic regions cannot be defined by standard pre-treatment computed tomography scans. Hendrickson et al identified hypoxic sub-volumes of head and neck tumors in patients using FMISO-PET imaging and created example plans to simulate boosts of an additional 10 Gy on the prescribed 70 Gy to the primary tumor via intensity-modulated radiation therapy (IMRT) to explore the feasibility and efficacy of this approach (93). They estimated a significant increase of 17% in tumor control probability without unacceptable increases in normal tissue complication probability with this treatment technique (Fig.…”
Section: Non-invasive Hypoxia Imagingmentioning
confidence: 99%